Operationalisation of Hybrid Peacebuilding in Asia From Theory to Practice - Uesugi, Yuji; Deekeling, Anna; Umeyama, Sophie Shiori; McDonald-Colbert, Lawrence (Security, Development and Human Rights in East Asia, 2021)
This open access book explores common critiques in the literature of hybrid peacebuilding, especially the lack of connection between hybridity in theory and practice. Through using a complexity-informed framework, the foundation for introducing the mid-space actor typology is established. Mid-space actors as insider-partial mediators are perceived to be vital agents for peace processes in conflict-affected areas and thus can be important power brokers and focal points for outside actors. In this book, two insider views are examined through analysing mid-space actors in the peacebuilding process in Cambodia and in Mindanao, the Philippines. First, it explores the process of identity-building of Cambodian monks and how such a process enables or hinders the monks to bridge existing cleavages. Then, in the case study of Mindanao, the roles of civil society actors are considered. The next step is to introduce the outsider's perspective on hybrid peacebuilding and how Asian peacebuilding actors such as China and Japan are engaging with mid-space actors who provide key bridges in peacebuilding.